Rabies seropositive individuals, dogs, and healthcare professionals without prior vaccination in four Brazilian Indigenous communities. - Matheus Lopes Ribeiro; Camila Michele Appolinario; Bruna Letícia Devidé Ribeiro; João Henrique Farinhas; Fernando Rodrigo Doline; Gisely Toledo Barone; Juliana Amorim Conselheiro; Vamilton Alvarés Santarém; Leandro Meneguelli Biondo; Andrea Pires Dos Santos; Rogério Giuffrida; Louise Bach Kmetiuk; et al. (PLoS Neglected Tropical Diseases)
Indigenous communities are reportedly among the most vulnerable populations exposed to rabies worldwide. Accordingly, this study aimed to assess rabies serum titers from healthy Indigenous individuals, their dogs, and healthcare professionals of four Indigenous communities from São Paulo state, southeastern Brazil. Blood samples were collected, and an epidemiological questionnaire applied. The samples were processed by Fluorescent Antibody Virus Neutralization (FAVN) method. Overall, 35/299 (11.7%) individuals and 22/166 (13.2%) dogs without prior vaccination were seropositive. Furthermore, 4/18 (16.7%) healthcare professionals were seropositive, with only one reporting prior rabies vaccination. The lack of rabies titers in the remaining 14/18 (77.8%) healthcare professionals indicates no immune protection. Seropositivity was associated with being from the Kopenoty community (p = 0.026) and with owners reporting seeing their dogs in contact with bats (p = 0.022). In summary, these results should be considered as a warning for the risk of human-dog rabies exposure and infection, mainly due to bat contact.